Photosynthetic Microbial Desalination Cell to Treat Oily Wastewater Using Microalgae Chlorella Vulgaris - Suhad Shamil Jaroo; Ghufran F. Jumaah; Talib R. Abbas (Civil Engineering Journal, 2019)
Microbial desalination cell (MDC) offers a new and sustainable approach to desalinate saltwater by directly utilizing the electrical power generated by bacteria during organic matter oxidation. In this study, we used microalgae Chlorella Vulgaris in the cathode chamber to produce oxygen as an electron accepter by photosynthesis process for generate bioelectricity power and treat oil refinery wastewater by microorganisms in both anode and cathode.The power density generated by this Photosynthetic Microbial Desalination Cell (PMDC) with 1KΩ external resistance at the first 4th hr. of operation period was 0.678 W/m3 of anode volume and 0.63 W/m3 of cathode volume. It increased after one day to a peak value of (4.32 W/m3 of anode volume and 4.013 W/m3 of cathode volume). The microalgae growth in the biocathode chamber followed in terms of optical density. The optical density increased from 0.546 at the beginning of the system operation to 1.71 after 24 days of operation period. The percentage removal of chemical oxygen demand (COD) of oil refinery wastewater was 97.33% and 79.22% in anode and cathode chamber, respectively. The microalgae in the biocathode were able to remove volatile compounds causing odor from the influent wastewater. TDS removal rate 159.722 ppm/h with initial TDS in desalination chamber of 35000 ppm.